Peran Machine Learning Dalam Pembelajaran Di LKP Bintang Mulia Batu Bara - Rahmadani, Nurul; Kurniawan, Edi; Risnawati, Risnawati (STMIK Royal, 2023)
LKP Bintang Mulia Batu Bara is located in a coastal area which resulted in the guidance participants not being updated on technological advances in the education sector. Even though the times have been very advanced with one of the newest innovations, namely Machine Learning. Machine Learning in the field of education can provide a variety of learning options, so that students can find what is best for them, taking into account the differences of each individual student. Machine Learning can also be used to monitor learning processes that confuse students, so that Machine Learning in education runs in harmony with what students need. The purpose of doing this service is to broaden students' understanding of the role of Machine Learning in learning. This service was held on April 15, 2023, and the participants in this activity were 8 LKP guidance students. So the result of this dedication is that there are many roles that Machine Learning can play in learning, such as playing a role in learning content, the teaching process, giving assignments, the assessment process, and monitoring student learning progress. Keywords: education; learning; Machine LearningAbstrak: LKP Bintang Mulia Batu Bara terletak di daerah pesisir pantai yang mengakibatkan para peserta bimbingan tidak update mengenai kemajuan teknologi di bidang pendidikan. Padahal perkembangan zaman sudah sangat maju dengan salah satu inovasi terbaru, yaitu Machine Learning. Machine Learning di bidang pendidikan dapat memberikan berbagai pilihan pembelajaran, sehingga siswa dapat menemukan apa yang terbaik bagi mereka, dengan mempertimbangkan perbedaan tiap individu siswa. Machine Learning juga dapat digunakan untuk memonitoring proses pembelajaran yang membingungkan siswa, sehingga Machine Learning dalam pendidikan berjalan selaras dengan yang dibutuhkan siswa. Tujuan dilakukannya pengabdian ini ialah untuk memperluas pemahaman siswa mengenai peran Machine Learning dalam pembelajaran. Pengabdian ini dilaksanakan pada tanggal 15 April 2023, dan yang menjadi peserta dalam kegiatan ini ialah para siswa-siswi bimbingan LKP yang berjumlah 8 orang. Maka hasil dari pengabdian ini ialah banyak peran yang dapat dilakukan Machine Learning dalam pembelajaran, seperti berperan dalam konten pembelajaran, proses pengajaran, pemberian tugas, proses penilaian, serta memantau kemajuan belajar para siswa.Kata kunci: Machine Learning; pembelajaran; pendidikan